Malignant transformation of endometriosis in a laparoscopic trocar site a case report - Ling Han; Bingyi Zhang (BMC, 2022)
Abstract Background Malignant transformation of endometriosis is infrequent at the laparoscopic trocar site. Although malignant transformation is uncommon, it must be acknowledged in order to achieve radical resection. Case presentation We report on a 54-year-old woman with trocar site endometriosis 2 years after laparoscopic ovarian endometrial resection. Physical examination revealed a subcutaneous solid tumor with a diameter of 3 cm surrounding the scar of laparoscopic surgery in the right lower abdomen. Transabdominal ultrasonography showed a cystic tumor in the subcutaneous adipose layer of the right lower abdomen. The pathological diagnosis was poorly differentiated endometrioid carcinoma. Hysterectomy, bilateral salpingo-oophorectomy and pelvic lymphadenectomy were then performed. Histological examination revealed mixed endometrioid carcinoma and clear cell carcinoma. After six cycles of chemotherapy, computed tomography showed no signs of recurrence. Conclusions Malignant transformation of laparoscopic endometriosis is very uncommon, and the diagnosis and stage are determined by clinical manifestations and imaging examination. The main therapy methods are radical surgery combined with neoadjuvant chemotherapy and adjuvant radiotherapy. At the same time, reducing iatrogenic abdominal incision implantation is an effective prevention method.